Effect of lung protective ventilation on perioperative pulmonary infection in elderly patients with mild to moderate COPD under general anesthesia. Issue 2 (February 2020) - Ji, Xiaochen; Cui, Wenbin; Zhang, Boya; Shan, Shiqiang
Abstract: Objective: The research aims to explore the effects of different ventilation time on postoperative pulmonary infection in elderly patients with the mild and moderate chronic pulmonary obstructive disease (COPD), so as to provide evidence for reducing postoperative pulmonary infection complications in patients with COPD. Methods: 120 elderly patients with mild and moderate COPD were selected as the research objects. First, the general information of patients with COPD before surgery and the difference between healthy population and lung forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), FEV1/FVC and maximum midexpiratory flow (MMEF) functional indexes were analyzed and detected. Patients with COPD were operated on with single lung ventilation and general anesthesia. Patients with mild and moderate COPD were divided into two groups according to lung ventilation time (ventilation time 1.0–2.0 h group, ventilation time >2.0 h group). The inflammatory factors of IL-6, IL-21, TNF-α, and CXCL13 as well as inflammatory indicators of polycaprolactam (PCT), C-reactive protein (CRP) and white blood cell (WBC) in serum of all patients were detected after the operation. The probability of pulmonary infection after COPD was diagnosed and analyzed. Finally, the regression analysis of postoperative pulmonary infection in COPD patients was analyzed. Results: (1) The results showed that the smoking rate of mild and COPD patients was significantly higher than that of healthy people (P < 0.05). (2) The lung function indexes of the mild and moderate groups were significantly lower than those of the control group (P < 0.01), while the lung function indexes of the moderate group were significantly lower than those of the mild group (P < 0.05). (3) All the inflammatory indicators of moderate COPD patients were significantly higher than those of mild COPD patients (P < 0.05). (4) All inflammation-related indicators in patients with mild and moderate COPD with ventilation time of >2.0 h were significantly higher than those in the 1.0–2.0 h group (P < 0.05). (5) The probability of postoperative pulmonary infection in moderate patients was significantly higher than that in mild patients (P < 0.01). The probability of postoperative pulmonary infection in >2.0 h group was significantly higher than that in the 1.0–2.0 h group (P < 0.01). (6) Multivariate Logistic regression analysis results showed that lung function, duration of lung ventilation and smoking were independent risk factors for postoperative pulmonary infection in COPD patients. Conclusion: It is important to detect pulmonary function before surgery, maintain single lung ventilation protection for no more than 2.0 h during surgery, and quit smoking to improve pulmonary infection in patients with COPD after surgery. In addition, the incidence of postoperative pulmonary infection in patients with moderate COPD was higher than that in patients with mild COPD, suggesting that early treatment in patients with COPD was also of great significance in reducing the incidence of postoperative pulmonary infection.